ANALISIS EFISIENSI TEKNIS PENANGKAPAN IKAN MENGGUNAKAN ALAT TANGKAP PURSE SEINE DI MUNCAR, JAWA TIMUR - Eko Sri Wiyono TIP (Jurnal Teknologi Industri Pertanian, 2012)
Sardine (Sardinella lemuru) fisheries in Bali Straits has been questioned in term of its sustainability due to its declining harvest in last several years. This condition created a big impact to fishing activity and fish processing industry. To solve this problem, it is necessary to find out the solutions. The objective of this study was to calculate technical efficiency of purse seine fishing effort in the Bali Strait. This idea was based on the fact that the classical model of fisheries management that has been applied were not provide optimum results. If the conventional fisheries management in the last decades was approached from biological aspect, this study attempted to approach it from fishing efforts,i.e. the technical efficiency of fishing effort. The efficiency of fishing effort was calculated by using the Data Envelopment Analysis (DEA) method. The study has been conducted in Muncar, focusing on purse seine fishing gear which was used to capture sardine. The results of this study indicated that the fishing effort using purse seine in the Bali Straits, especially in Muncar, was inefficient. The variable inputs which used to capture sardine was not reached an optimum value. Furthermore, in order to manage purse seine fisheries in Bali Strait, the results of this study were used as an alternative to the management of purse seine fisheries in the Bali Strait.Keywords: Bali strait, DEA, purse seine, sardine, technical efficiency